Prognostic utility of carotid ultrasound and cardiac SPECT imaging in coronary artery bypass patients - Boshevski Marijan; Peovska, I; Maksimovic, J; M. Vavlukis; Meskovska, S (VIA MEDICA, 2006)
The aim of our study was to evaluate the role of myocardial perfusion imaging (MPI) and common carotid artery intima-media thickness (CCA IMT) in the prognosis of patients with coronary artery disease referred for coronary artery bypass surgery (CABG) in a newly made prognostic model.
Keywords: coronary artery disease; CABG; SPECT myocardial perfusion; carotid ultrasound